Advertising Communication in Electronic Discourse - Muradyan, Gayane (Armenian Folia Anglistika, 2007)
The discourse of e-advertising which is considered a functional-stylistic expression of Modern English is characterized by a number of features: the abundant use of metaphoric expressions, short sentences, literary cuts, verbs in the active voice and the use of lexical units with positive or extremely negative meanings.